Herbal drug discovery for the treatment of nonalcoholic fatty liver disease - Tingting Yan; Nana Yan; Ping Wang; Yangliu Xia; Haiping Hao; Guangji Wang; Frank J. Gonzalez (Elsevier, 2020)
Few medications are available for meeting the increasing disease burden of nonalcoholic fatty liver disease (NAFLD) and its progressive stage, nonalcoholic steatohepatitis (NASH). Traditional herbal medicines (THM) have been used for centuries to treat indigenous people with various symptoms but without clarified modern-defined disease types and mechanisms. In modern times, NAFLD was defined as a common chronic disease leading to more studies to understand NAFLD/NASH pathology and progression. THM have garnered increased attention for providing therapeutic candidates for treating NAFLD. In this review, a new model called "multiple organs-multiple hits" is proposed to explain mechanisms of NASH progression. Against this proposed model, the effects and mechanisms of the frequently-studied THM-yielded single anti-NAFLD drug candidates and multiple herb medicines are reviewed, among which silymarin and berberine are already under U.S. FDA-sanctioned phase 4 clinical studies. Furthermore, experimental designs for anti-NAFLD drug discovery from THM in treating NAFLD are discussed. The opportunities and challenges of reverse pharmacology and reverse pharmacokinetic concepts-guided strategies for THM modernization and its global recognition to treat NAFLD are highlighted. Increasing mechanistic evidence is being generated to support the beneficial role of THM in treating NAFLD and anti-NAFLD drug discovery. Key words: Natural products, Fatty liver, Metabolic syndrome, TCM, NAFLD